Control of hyperphosphatemia in regular hemodialysis (HDx) patients by calcium acetate (CA) versus calcium carbonate (CC). A double blind crossover prospective study - Sharaf EI Din, U A A; Mansour, M; El Hamamsy, M; El Ghonaimy, E H G; Mansour, L A (African Journal of Nephrology, 2016)
This study included fourty chronic renal failure patients aged 37-83 years (mean 51.3±7) on thrice weekly HDx for 4-144 month (Kt/V >1.2). Acetate dialysate with calcium concentration of 3 mEq/L was used. All phosphate binders were discontinued for one month. Patients were divided in two groups. Group I (20 cases) received CA, while group II (20 cases) received CC in equimolar dose (10 mmol, of either t.i.d.) for one month. Crossover of treatment was done for another month while keeping patients on the same diet. Serum levels of total calcium (Ca), ionized Ca (iCa), phosphorus (P), alkaline phosphates (AP), urea (U), creatinine (Cr), ALT, AST, total proteins (TP) and albumin (Alb) were estimated before, and at the end of each month of CA and CC treatment. Serum Ca and iCa were significantly lower in group I after CA compared to values after CC (p<0.01). Similar results in Ca levels were observed in group II (P<0.05). In group II only serurn P was significantly lower after CA compared to its values after CC (P<0.05). There was no significant difference in AP, U, Cr, ALT, AST, TP and Alb before, and at the end of each month of CA and CC treatment (P>0.05 in all). We excluded 12.5% of cases due to CA intolerance while non of cases had similar intolerance to CC. Conclusion: 1) CA is not very superior to CC in control of hyperphosphataemia. 2) CA can be safely increased without the risk of hypercalcemia. 3) Active Vitamin D and high dialysate Ca can be used to suppress parathyroid activity more safely with CA than with CC. 4) Tolerability to CC is superior.